Prospective of the nursing approach to sustainability within the framework of the Sustainable Development Goals for 2030 - Rodríguez López, Javier Isidro (2022)
Objective: To determine the prospective scenario for nursing in the approach to sustainability in the framework of the Sustainable Development Goals for the year 2030 from the perception of a group of nursing professionals in Mexico. Method: Prospective, cross-sectional study, with a census sample of (n=18) of the total number of students in a master's degree program in nursing sciences at a Mexican university. The prospective questionnaire ODSENF V1 and a sociodemographic data form were used for data collection. Informed consent was signed. Data were analyzed using descriptive statistics. Main Results: In the overall picture nursing professionals are conceived to be linked in their axes of action in an acceptable scenario at a 10-year projection. General conclusion: The prospective scenario for the nursing approach to the Sustainable Development Goals (SDGs) shows a greater proximity to the target image of the people category, possibly due to the relationship of the nursing professional with the social determinants of health that intervene in the well-being of populations, the planet category is in an acceptable scenario for its approach, The prosperity and alliances categories are the least linked to 2030, this could be due to the lack of clarity in the ecological concepts and not relating them to their hospital operational disciplinary actions, which requires urgent educational processes and generation of competencies for sustainability at all levels of nursing education.